Parental Sex and Not Kinship Determines Egg Cannibalism in Arma custos Fallou (Hemiptera: Pentatomidae: Asopinae) - Wu, Shaolong; Zeng, Weiai; Deng, Wan; Li, Jiaying; Li, Mi; Tan, Lin; Cai, Hailin; Li, Xiaohong; Li, Youzhi; Zhou, Zhicheng (Frontiers in Ecology and Evolution, 2022)
Background Arma custos Fallou (Hemiptera: Asopinae) is an important predatory insect native to China, South Korea, and Mongolia. It is important to understand the evolution of egg cannibalism in A. custos to evaluate the biocontrol potential of this species. However, few reports have suggested egg cannibalism in A. custos, and whether hungry adult A. custos males and females prey on their eggs remains unknown. Here, we investigated the effects of the parental sex of A. custos adults on egg cannibalism of parental and non-parental eggs (kinship) under no-choice and free-choice conditions, along with the effects of predator and egg density on egg cannibalism under starvation conditions. Results Females frequently visited and cannibalized a higher proportion of eggs, whereas males almost did not participate in egg cannibalism (less than 17% males showed egg cannibalism behavior). Moreover, regardless of their relationship with the egg, neither male nor female adults consumed all available eggs even in the absence of an alternative food source, and >70% of eggs remained unconsumed. In contrast, cannibalistic males and females did not discriminate between parental and non-parental egg types. Meanwhile, cannibalism rates were similar when adults were offered 30 eggs or more. However, when offered fewer than 30 eggs, cannibalism rates declined disproportionally, suggesting that limited egg availability reduced cannibalism. Additionally, the lifespan of A. custos adult females increased significantly with increasing number of consumed eggs (p < 0.05). Conclusion Arma custos females exhibit a higher tendency for egg cannibalism than males. Neither male or female A. custos discriminated between parental and non-parental egg types. Cannibalism enhances survival in that a starved individual who predates on eggs survives similarly to a well-fed individual. These findings provide a model to study the evolution and biological significance of egg cannibalism in A. custos and also contribute to the efficient mass rearing and realization of A. custos for biological control.